2018
DOI: 10.1111/1747-0080.12411
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grandparents on the dietary intake of their 2–12‐year‐old grandchildren: A systematic review

Abstract: Grandparents in caregiving roles may negatively influence the dietary intake and weight status of their grandchildren. More rigorous, targeted studies are required to further define the mechanisms by which grandparents' knowledge, attitudes and feeding behaviours may influence child dietary intake. This review suggests that grandparents may be an important audience to target in future child nutrition interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 50 publications
(257 reference statements)
2
49
0
4
Order By: Relevance
“…This may be due to generational differences in feeding practices. Recent studies highlighted the extent to which grandparents are often responsible for feeding children meals and snacks, 27,28 and their potential role in the development of obesity. 29 One prior study found that both tension and conflict existed between parents and grandparents related to child feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to generational differences in feeding practices. Recent studies highlighted the extent to which grandparents are often responsible for feeding children meals and snacks, 27,28 and their potential role in the development of obesity. 29 One prior study found that both tension and conflict existed between parents and grandparents related to child feeding.…”
Section: Discussionmentioning
confidence: 99%
“…29 One prior study found that both tension and conflict existed between parents and grandparents related to child feeding. 28 Grandparents may be more likely to indulge children with less healthy foods, to overfeed, and to perceive heavy children as healthy children. 25 There is further evidence that preschoolers cared for by relatives were more likely to be obese, compared with children in other care arrangements, although grandparent care specifically was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…11 With the awareness that grandparents are increasingly involved in the care of their grandchildren, the systematic review by Young et al addresses a potentially important aspect of determinants of children's dietary intakes. 4 Studies where grandparents provided care to 2-12-year-olds were considered, excluding where grandparents were primary caregivers and studies from developing countries. Studies were eligible for inclusion if they had reported outcomes on the children's dietary intake and weight, and the grandparent's knowledge and beliefs on nutrition or their feeding practices.…”
Section: Editorialmentioning
confidence: 99%
“…With the awareness that grandparents are increasingly involved in the care of their grandchildren, the systematic review by Young et al . addresses a potentially important aspect of determinants of children's dietary intakes . Studies where grandparents provided care to 2–12‐year‐olds were considered, excluding where grandparents were primary caregivers and studies from developing countries.…”
mentioning
confidence: 99%
“…In recent years, the presentation of systematic reviews in Australia has increased potentially associated with increasing academic capacity . However their publication in Nutrition & Dietetics was limited to just four systematic reviews in 2018 to 2019 . Thank you to the authors of conference abstracts who responded to our invitation to submit their systematic review through expedited peer‐review.…”
mentioning
confidence: 99%